Defining Waka Musically - Hepburn, Christopher. author. aut Link
XXIII, 100 p. 12 illus.
Keywords: This book considers how music, musicality, and ideologies of musicality are working within the specific construction of waka on the theme of male love in Kitamura Kigin’s Iwatsutsuji (1676) and Ihara Saikaku’s Nanshoku ōkagami (1687) by using a modified generative theory of music. This modified theory seeks to get at the interdependent meanings that may exist among the music, image, and the text of the waka in question. In all, this study guides the reader through five waka on the theme of male love and demonstrates not only how each waka is inherently musical but how the image and text may interdependently relate to the ways in which premodern Japanese song poets may not only have thought in and with sound but may have also utilized a diverse array of musical gestures to construct new objects of knowledge. In the case of this study, these new objects of knowledge seem to have aided in situating a changing musicopoetics that aligned with changing constructions of male desire. .